Introgression Threatens the Genetic Diversity of Quercus austrocochinchinensis (Fagaceae), an Endangered Oak: A Case Inferred by Molecular Markers - An, Miao; Deng, Min; Zheng, Si-Si; Jiang, Xiao-Long; Song, Yi-Gang (Frontiers in Plant Science, 2017)
Natural introgression can cause negative effects where rare species experience genetic assimilation and invade by their abundant congeners. Quercus austrocochinchinensis and Q. kerrii (subgenus Cyclobalanopsis) are a pair of closely related species in the Indo-China area. Morphological intermediates of the two species have been reported in this region. In this study, we used AFLP, SSR and two key leaf morphological diagnostic traits to study the two Q. austrocochinchinensis populations, two pure Q. kerrii and two putative hybrid populations in China. Rates of individual admixture were examined using the Bayesian clustering programs STRUCTURE and NewHybrids, with no a priori species assignment. In total, we obtained 151 SSR alleles and 781 polymorphic loci of AFLP markers. Population differentiation inferred by SSR and AFLP was incoherent with recognized species boundaries. Bayesian admixture analyses and principal coordinate analysis identified more hybrids and backcrossed individuals than morphological intermediates in the populations. SSR inferred a wide genetic assimilation in Q. austrocochinchinensis, except for subpopulation D2 in the core area of Xi-Shuang-Ban-Na Nature Reserve (XSBN). However, AFLP recognized more Q. austrocochinchinensis purebreds than SSR. Analysis using NewHybrids on AFLP data indicated that these hybridized individuals were few F2 and predominantly backcrosses with both parental species. All these evidences indicate the formation of a hybrid swarm at XSBN where the two species co-exist. Both AFLP and SSR recognized that the core protected area of XSBN (D2) has a high percentage of Q. austrocochinchinensis purebreds and a unique germplasm. The Hainan population and the other subpopulations of XSBN of the species might have lost their genetic integrity. Our results revealed a clear genetic differentiation in the populations and subpopulations of Q. austrocochinchinensis and ongoing introgression between Q. austrocochinchinensis and Q. kerrii at the disturbed contact areas. Combining the results from genetic and morphological analyses, the conservation of subpopulation D2 should be prioritized. Conservation and restoration of the integrity of tropical ravine rainforest is an important long-term goal for the successful conservation of Q. austrocochinchinensis. The fine-scale landscape might play an essential role in shaping the spatial patterns of hybridization. Further studies are needed to evaluate these patterns and dynamics.